On managing projects and initiatives - Blaker, Lyle; Hendrix, Kitty (Ascent Audio, 2024)
Everyone is now a project leader-learn how to manage them more effectively. If you read (or listen to) nothing else on managing projects and initiatives, listen to these ten articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you lead initiatives that will inspire your people, tackle your biggest challenges with agile, and prepare yourself and your organization for a world driven by projects. This book will inspire you to reap benefits from your initiatives more quickly; become a better project sponsor; kill initiatives that aren't performing; navigate the politics of innovation projects; keep AI and digital transformation on track; and prepare for the next generation of project management tools. HBR's 10 Must Reads series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. The series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself.
Online resource; title from title details screen (O'Reilly, viewed July 2, 2024)
Keywords: Project management; Gestion de projet; Audiobooks; Livres audio